2007
DOI: 10.5694/j.1326-5377.2007.tb00905.x
|View full text |Cite
|
Sign up to set email alerts
|

Homicide during psychotic illness in New South Wales between 1993 and 2002

Abstract: Objective: To review homicides committed during psychotic illness in New South Wales over 10 years from 1993 to 2002. Design and setting: Case series of all known homicides committed during psychotic illness in NSW, taken from reports of psychiatrists submitted in proceedings in the Supreme Court of NSW. Main outcome measures: Demographic and clinical features of perpetrators; estimated frequency of homicide during psychotic illness. Results: In the 10 years from 1993 to 2002, there were at least 88 people cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
89
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 18 publications
(28 reference statements)
4
89
1
3
Order By: Relevance
“…We used a narrower definition of homicides occurring as a result of psychotic illness. This was possible because we were able to obtain psychiatric reports in all cases, which provided detailed information about the circumstances and reasons for each homicide in this category 16 . Finally, we examined the homicides of children aged under 1 year.…”
Section: Methodsmentioning
confidence: 99%
“…We used a narrower definition of homicides occurring as a result of psychotic illness. This was possible because we were able to obtain psychiatric reports in all cases, which provided detailed information about the circumstances and reasons for each homicide in this category 16 . Finally, we examined the homicides of children aged under 1 year.…”
Section: Methodsmentioning
confidence: 99%
“…However, they also perpetrate acts of violence 28,29. This is particularly evident during the FEP3032 and during the first year of illness 33. Data from a large-scale United Kingdom study of FEP cases indicated that nearly 40% of participants were aggressive at first service contact, with more than one-half reported as being physically violent 32.…”
mentioning
confidence: 99%
“…Olav Nielsen ( Bispebjerg University Hospital, Copenhagen, Denmark) presented data from an Australian sample of homicides (Nielssen et al, 2007); 61% were first episode psychosis (FEP). Most homicides were in response to frightening delusions and command hallucinations were rare.…”
Section: Epidemiology (Reported By Charlotte Gayer-anderson Andrementioning
confidence: 99%